Pulmonary Tuberculosis Nursing Care with Management of Airway Clearance: Case Study - Surya Pratama, Erlangga; Wahyudi, Iwan (Nursing Case Insight Journal, 2024)
Pulmonary tuberculosis is a contagious infectious disease with the highest prevalence in the world and the third largest in Indonesia with 10.4 million cases each year. Transmission occurs when a sufferer coughs or sneezes and the sufferer accidentally spreads germs into the air in the form of droplets. A person suffering from pulmonary tuberculosis can infect 10-15 people around him. Therefore, infectious disease management needs to be carried out as an effort to control several disease risk factors to maintain and improve public health. Objective: This case study aims to test the effectiveness of implementing effective coughing as a management method for ineffective airway clearance in pulmonary tuberculosis sufferers. Method: The method used is a case study by taking anamnesis, observation, physical examination and medical records. The participant in this study was Mr. R with pulmonary tuberculosis. Results: The results of this case study show that Effective coughing exercises are useful for managing airway clearance in pulmonary tuberculosis sufferers, this is characterized by sputum that can be expelled through the mouth, which is characterized by reduced shortness of breath, normal respiratory frequency, regular breathing rhythm, no additional breath sounds. Therefore, cough training has been empirically proven to be effective in managing airway clearance in pulmonary tuberculosis patients. Recommendation: Effective coughing can only be applied to pulmonary tuberculosis patients with shortness of breath, cough with phlegm, rhonchi breath sounds, and complaints that sputum is difficult to expel.